2021
DOI: 10.1007/s11033-021-06807-x
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin-d alleviates hepatic fibrosis through regulating GPER1/autophagy signaling

Abstract: Background Hepatic fibrosis is the final pathway of chronic liver disease characterized by excessive accumulation of extracellular matrix (ECM), which eventually develop into cirrhosis and liver cancer. Emerging studies demonstrated that Saikosaponin-d (SSd) exhibits a protective role in liver fibrosis. However, the mechanism underlying anti-liver fibrosis of SSd in vivo and in vitro remains unclear. Methods and results Transforming growth factor (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Similarly, Sirius red and Masson staining showed that saikosaponin-d alleviated liver fibrosis. [23] LSECs are highly specialized endothelial cells that line the intrahepatic blood and other cells in the liver and play an important role in sustaining liver homeostasis. [4] LSECs are characterized by the absence of a basal membrane and the presence of open channels called fenestrae, making them extremely permeable.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sirius red and Masson staining showed that saikosaponin-d alleviated liver fibrosis. [23] LSECs are highly specialized endothelial cells that line the intrahepatic blood and other cells in the liver and play an important role in sustaining liver homeostasis. [4] LSECs are characterized by the absence of a basal membrane and the presence of open channels called fenestrae, making them extremely permeable.…”
Section: Discussionmentioning
confidence: 99%
“…In a study based on a tert-butyl hydroperoxide (TBHP)-induced oxidative stress model of NPC, quercetin was found to enhance autophagy through AGING modulation of the p38MAPK/mTOR signaling pathway to protect NPC from apoptosis and thus delay cellular senescence [139]. Caihu saponin D was discovered to reduce the release of inflammatory factors in mice in a study based on carbon tetrachloride-induced liver fibrosis in mice through enhancing autophagy [140].…”
Section: Bupleurum Scorzonerifolium and Its Compounds Delay Cellular ...mentioning
confidence: 99%
“…Its targeting reduces the expression of α-SMA, TGF-β, and collagen I [114] Adenosine A3 receptor (A3-AR) G i Mediates pro-fibrotic and pro-inflammatory response by regulation of the PI3K/NF-κB/Wnt/βcatenin signaling pathway [115] G protein-coupled estrogen receptor 1 (GPER) G i Represses activation of HSCs and its autophagy mechanism. Also, decreases the expression of IL-6 by BMM, preventing fibrosis [116,117] G-protein-coupled bile acid receptor 91 (GPR91) G i Succinate-induced activation leads to increased expression of α-SMA, TGF-β, and collagen I in HSCs [118] Neuropeptide Y receptor Y1 (Y1-R) G i Activation induces phosphorylation of mTOR, p70S6K, and 4EBP1 in HSCs leading to fibrosis [119] Lysophosphatidic acid receptor 1 (LPAR1) G i Enables activation and differentiation of HSCs into myofibroblast leading to actin rearrangement and proliferation while inhibiting HSC apoptosis [120] Smoothened receptor (SMO) G i Transduces the Hedgehog pathway resulting in EMT of the HSCderived myofibroblasts supporting their pro-fibrogenic phenotype [121] Frizzled receptor 2 (Fz2) G i Leads to the expression of collagen I and TGF-β leading to the differentiation of HSCs into myofibroblast [122] C5a receptor (C5aR) G i Activates HSCs to produce α-SMA, hyaluronic acid, and collagen IV while inhibiting apoptosis of TNF-α and ligand-induced HSC apoptosis [123] Apelin receptor G i Leads to the expression of pro-fibrotic genes like α-SMA and collagen I via the ERK signaling pathway [124] M2 acetylcholine receptor (M2) G i Induces HSC hyper-proliferation and upregulation of pro-fibrotic markers such as collagen I and TGF-β a [97] M3 acetylcholine receptor (M3) G q Agonist-mediated activation alleviates HSC activation, collagen deposition, pro-fibrotic and pro-ECM markers, diminishing liver injury a [98] Angiotensin II type 1 receptor (AT1R) G q Supports activation of HSCs and fibrosis via phosphorylation of JAK2 and following activation of RhoA/Rho-kinase [125] α1Aadrenoreceptor (ADRA1A) G q Expressed by activated HSCs, upregulates secretion of NF-κB, inducing pro-inflammatory phenotype, and increased HSC contraction [126] Serotonin receptor 1B (5-HT1B) G q Upregulated in activated HSCs requiring investigation into its specific role in fibrosis progression [127] Serotonin receptor 2A (5-HT2A) G q Antagonists decreased the activation of HSCs, expression of profibrotic markers, and inflammatory markers [128] Arginine vasopressin receptor 1A (AVPR1A) G q Induces increase in intracellular calcium and enhanced MAPK activity mediating HSC proliferation and contraction [129] Endothelin receptor type A (ETAR) G q Upregulated in activated HSCs expressing α-SMA. In-depth implications and associated signaling pathways need ...…”
Section: Receptor Name G Protein Family Function In Liver Fibrosis Re...mentioning
confidence: 99%